Low fat diet versus low carbohydrate diet for management of non-alcohol fatty liver disease: A systematic review - Varkaneh, Hamed Kord; Poursoleiman, Faezeh; Al Masri, Mohammad Khaldoun; Alras, Kamar Allayl; Shayah, Yamen; Masmoum, Mohd Diya; Alangari, Fulwah Abdulaziz; Alras, Abd Alfatah; Rinaldi, Giulia; Day, Andrew S.; Hekmatdoost, Azita; Abu-Zaid, Ahmed; et al. (Frontiers in Nutrition, 2022)
Although there is a consensus on beneficial effects of a low calorie diet in management of non-alcoholic fatty liver disease, the optimal composition of diet has not yet been elucidated. The aim of this review is to summarize the results of current randomized controlled trials evaluating the effects of low fat diet (LFD) vs. low carbohydrate diet (LCD) on NAFLD. This is a systematic review of all the available data reported in published clinical trials up to February 2022. The methodological quality of eligible studies was assessed, and data were presented aiming specific standard measurements. A total of 15 clinical trial studies were included in this systematic review. There is an overall lack of consensus on which dietary intervention is the most beneficial for NAFLD patients. There is also an overall lack of consensus on the definition of the different restrictive diets and the percentage of macronutrient restriction recommended. It seems that low calorie diets, regardless of their fat and carbohydrate composition, are efficient for liver enzyme reduction. Both LCD and LFD have similar effects on liver enzymes change; however, this improvement tends to be more marked in LFD. All calorie restrictive dietary interventions are beneficial for reducing weight, liver fat content and liver enzymes in individuals with NAFLD. Low fat diets seem to be markedly successful in reducing transaminase levels. Further research is needed to explore diet intensity, duration and long-term outcome.